Machado de Assis: Formação e Autonomia Literária em Memórias Póstumas de Brás Cubas - Brito, Isabel Mônica Souza de (2010)
This study tries to consider the literary text on the basis of the three main instances of literary communication: author, work and reader. The first chapter exposes the general conditions that make possible the appearance and the development of Machado de Assis and his work, taking into consideration the material conditions according to what author and work integrate the broad field of cultural productions. It is based on the conception of literary field, developed by Pierre Bourdieu, analogous to that of literary system by Antonio Candido. The second chapter presents some of the compositional resources of which availed Machado de Assis himself. It discusses about several conceptualizations of intertextuality and influence, important conceptions with which deal the Comparative Literature. The main researchers, of whose studies it has been making use, are Sandra Nitrini and Tania Carvalhal, who systematized the conceptual notions of important theoreticians of Comparatistic, as well as the categories by Harold Bloom. The third chapter is dedicated to the work, on which our proposal of interpretation has been concentrated: Memórias póstumas de Brás Cubas (1881), by which, seeing that it is alike a key to the comprehension of the mature Machadian work, the writer has his literary autonomy asserted. It tries to investigate how Machado de Assis constructed the author-narrator of this work, who has emphasized the autoreflexive attitude that will be implicated within the narrative in the properties of temporality and affectivity. This autoreflexive attitude set the narrator Brás Cubas in search of himself, as it provides an intense dialogue among all tradition not only of literati but also of thinkers, situating the work in a vast ideological field. We have tried to make noticeable that this ideological field, just like it is represented in the work, constitutes one of the innovations of Machadian composition and, this way, confirms the originality and the expertise of the Brazilian author, whose work can be extended to several areas of Humanities.